HARMONIZATION OF QUALIFICATIONS IN HIGHER EDUCATION AND IN THE JOB MARKET - A. A. Shekhonin; V. A. Tarlykov; A. O. Voznesenskaya; A. V. Bakholdin (Высшее образование в России)
The paper highlights the development of the requirements to modern qualifications in education and in the job market based on professional standards in the conditions of the national qualification system formation. It is shown that the qualifications of graduates formed in the process of practical-oriented education taking into account professional standards, differ greatly form the qualifications used in the real sphere of professional activity. Harmonization of qualifications can be ensured by the correspondence between the level of a graduate’s qualifications and the requirements of labour market, and also by the efficiency of interaction between higher education institutions and employers.